МОНГОЛЫН ЦАЙР-ХАРТУГАЛГАНЫ ОРДУУДЫН АНГИЛАЛ - Д.ДОРЖГОТОВ (Geological Issues, 2023)
The classification of lead-zinc deposits and ore occurrences in Mongolia is mainly based on mineral association, rocks which are genetically related to Pb, Zn mineralization, host litology, ore structure, and alteration. The deposits and occurrences of lead-zinc mineralization in Mongolia in the report are classified into five ore formation: polymetal calcic skarn related to subalkaline granite, granosyenite, mezothermal lead-zinc related to subalkaline polyphase intrusions, mesothermal cupper-lead-zinc related to subaerial extrusive rocks, epithermal silver-lead related to felsic extrusive rocks and telethermal leaf fine formation in carbonate rocks. All ore formation of lead-zinc deposits can be subdhided into several models. The leader role belongs to tire Fe-Zn (Cd, In) skarn md mezothermal Zn-Pb-Ag (Au) models.